Improving interactive media education: Investigating the capabilities of educational podcasting platforms for enhanced learning - Parumo, Shahril; Rahim, Sarni Suhaila; Jusni, Khairul Yasser; Jali, Suriati Khartini (Little Lion Scientific Islamabad Pakistan, 2024)
This study examines the transformative potential of interactive educational podcasting platforms in higher education. These platforms employ digital technology to enhance learning experiences and address educational shortcomings. The study evaluates a specialized interactive educational podcasting platform designed to support higher education students by offering a variety of subjects and modules tailored for distinct disciplines in interactive media courses. An experiment involving 19 participants comprising subject matter experts, multimedia experts, and students was conducted to assess the platform’s effectiveness as a learning tool. The results indicate a positive impact on student engagement and learning outcomes. Interactive educational podcasting platforms provide personalized, accessible, and engaging learning experiences, presenting a significant opportunity to revolutionize higher education. Future research and collaboration will be crucial for optimizing these platforms and maximizing their potential to transform educational practices.